2020
DOI: 10.34067/kid.0000052020
|View full text |Cite
|
Sign up to set email alerts
|

Buttonhole Cannulation of Arteriovenous Fistulas in the United States

Abstract: The cannulation technique of a hemodialysis vascular access has remained controversial with differing viewpoints. The quality of dialysis, overall patient safety and individual dialysis experience often dictate the type of cannulation technique used in clinical practice. The three commonly used techniques to access a hemodialysis vascular access are the rope-ladder, area and buttonhole. Even though the buttonhole technique has been around since mid-1970's, the dialysis community remains divided on its suitabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 20 publications
0
11
0
1
Order By: Relevance
“…The kind of cannulation technique utilised in clinical practise is frequently determined by the standard of dialysis, overall patient safety, and a patient's personal experience with dialysis. The three methods-rope ladder, area, and buttonhole-that are often employed as hemodialysis vascular access are (Vachharajani et al, 2020) Regarding the Percentage distribution of participated groups regarding their socio-demographic data, the present study showed that the mean age among study and control groups was nearly similar percentages (62.9 ± 2.1 years, 61.8 ± 2.0 years) respectively. As regard to marital status; it was founded that more than half of studied group and one third of control group were married.…”
Section: Discussionmentioning
confidence: 54%
“…The kind of cannulation technique utilised in clinical practise is frequently determined by the standard of dialysis, overall patient safety, and a patient's personal experience with dialysis. The three methods-rope ladder, area, and buttonhole-that are often employed as hemodialysis vascular access are (Vachharajani et al, 2020) Regarding the Percentage distribution of participated groups regarding their socio-demographic data, the present study showed that the mean age among study and control groups was nearly similar percentages (62.9 ± 2.1 years, 61.8 ± 2.0 years) respectively. As regard to marital status; it was founded that more than half of studied group and one third of control group were married.…”
Section: Discussionmentioning
confidence: 54%
“…This technique has been advocated because it reduces pain and decreases the formation of aneurysms and hematomas. However, infection is the main complication mentioned [8,11,12,29]. The need to make a tunnel by the same nurse over the period of 4 or 5 weeks can also be an obstacle to the implementation of this technique.…”
Section: Advantages Disadvantagesmentioning
confidence: 99%
“…Three cannulation techniques for arteriovenous access for hemodialysis are available: area cannulation, rope-ladder cannulation, and buttonhole cannulation [2,8,9]. Area cannulation is associated with the appearance of a greater number of stenosis areas [4,10], whereas the buttonhole technique is associated with fewer hematomas and less pain during cannulation but higher infection rates [4,[11][12][13] and the ropeladder technique is associated with greater difficulty in cannulation, greater pain, and the formation of hematomas [11,14].…”
Section: Introductionmentioning
confidence: 99%
“…A limitation of our study is the low prevalence of some of the items on the WAHVAC instrument which limited assessment of reliability for these variables. For example, there were no patients in the buttonhole establishment phase which can be explained by it being a technique not common in Australia and predominantly used in Europe and Japan (Vachharajani et al, 2020). Another limitation to the study, is the number of area cannulations used, as area cannulations weaken the fistula wall (Parisotto et al, 2014).…”
Section: Implications For Clinical Practicementioning
confidence: 99%